NON-TRAUMATIC RIB FRACTURES, HAEMOTHORAX AND CHEST WALL HERNIA ASSOCIATED WITH EXCESSIVE COUGHING - Haider, Rehab; Ghassemi, Nader; Khan, Mahrukh; Ganaie, Muhammad Badar (Journal of Ayub Medical College Abbottabad, 2022)
Haemothorax is presence of blood in pleural cavity and is usually caused by chest trauma. Spontaneous rib fractures leading to haemothorax due to excessive coughing has seldom been described in the literature. We report an unusual case with asthma exacerbation who developed intense coughing followed by chest pain, breathlessness, and widespread bruising, without trauma or coagulopathy. Initial chest X-ray (CXR) and CT pulmonary angiogram (CTPA) showed no significant abnormality. CT scan on subsequent presentation showed left sided haemothorax with rib fractures. The patient was managed successfully with chest tube drainage. On follow up imaging, haemothorax resolved but he was found to have malunited rib fractures with chest wall hernia due to wide separation between ribs. He was referred to cardiothoracic surgeons for rib fixation and chest wall repair.